LONGAN PEEL EXTRACT (DIMOCARPUS LONGAN L.) AS AN ANTIOXIDANT AGAINST OXIDATIVE STRESS IN WISTAR RATS INDUCED BY TOXIC DOSES OF PARACETAMOL - Aulia Sandriani; Faizah Fulyani; Donna Hermawati; Santoso Santoso; Eva Annisaa (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Oxidative stress is an imbalance between free radicals and antioxidants, characterized by increase in malodialdehyde (MDA) levels. Stress oxidative caused by paracetamol overdose consumption and can be a serious problem for the structure and liver cell function. Oxidative stress prevented and controlled by antioxidant. Longan peel has phenolic and flavonoid which can potentially be sources of natural antioxidants. This study aimed to prove the longan peel extract had an antioxidant effect that could affect the oxidative stress in rats induced by toxic doses of paracetamol. Method: : Experimental research with control group design. Group P1, P2, and P3 were treatment group induced by paracetamol with a toxic dose of 2000 mg/kgBW and given extracts of longan peel (Dimocarpus longan L.) with multilevel doses, that were 25 mg/kgBW, 50 mg/kgBW, and 75 mg/kgBW wistar rat. Then, blood samples from each group were collected and measured plasma MDA levels and the animals were terminated, then their livers were taken for measurement of liver SOD enzyme activity. Result: One Way ANNOVA test showed a significant difference in plasma MDA (p=0,000) in the whole group of wistar rats. Significant differences were also shown on the examination of plasma MDA levels in the K1-K2, K2-P1, K2-P2, and K2-P3 groups (p<0,05). Conclusion: Longan peel extract had the effect of reducing plasma MDA levels of wistar rats induced by toxic doses of paracetamol compared to the control group.Keywords: Paracetamol, longan peel extract, MDA.